Marketing strategies on social media case study: Orchestra grupo5 - Nina, Aguiar Mariño,; Jurado, Karen Lizbeth Rocha; Naranjo, César Javier Ortiz (Edelweiss Applied Science and Technology, 2025)
The study analyzes the marketing and communication strategies implemented by the GRUPO5 orchestra, focusing on their impact, positioning, and audience connection through digital platforms, with a special emphasis on Instagram. The research employs a mixed methodology combining quantitative and qualitative analysis, which enables an understanding of how audience interactions and behaviors serve as key tools for applying these strategies. The study highlights how GRUPO5 has utilized a variety of formats, ranging from the publication of retrospective videos to collaborations with other artists, achieving an average engagement rate of 43% in the campaign selected as the case study, titled “50th ANNIVERSARY.” Additionally, it demonstrates that the use of interactive elements, campaign-specific hashtags, and emotional storytelling has strengthened the emotional bond with their audience. The analysis underscores that emotions play a crucial role in implementing effective hypermedia storytelling within content strategies. Furthermore, the application of segmentation strategies has allowed for greater impact by optimizing the creation of emotionally relevant content for the audience. This has enabled GRUPO5 to maintain its relevance in a competitive digital environment marked by constantly evolving consumer trends.